2018
DOI: 10.1186/s40644-018-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Mono, bi- and tri-exponential diffusion MRI modelling for renal solid masses and comparison with histopathological findings

Abstract: PurposeTo compare diffusion tensor imaging (DTI), intravoxel incoherent motion (IVIM), and tri-exponential models of the diffusion magnetic resonance imaging (MRI) signal for the characterization of renal lesions in relationship to histopathological findings.MethodsSixteen patients planned to undergo nephrectomy for kidney tumour were scanned before surgery at 3 T magnetic resonance imaging (MRI), with T2-weighted imaging, DTI and diffusion weighted imaging (DWI) using ten b-values. DTI parameters (mean diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Table 1 provides an overview of currently published values. One thing to note is that D2 reported in Riexinger et al 15 is roughly by 1 order of magnitude larger than the D2 values reported in the other publications, 5,10,11,13,14 which most likely can be attributed to the lower minimal b‐value used in Riexinger et al 15 The optimization performed here is based on the assumption that these large D2 values are a good representation of the real values and that consequently very small b‐values, say below 1 s/mm 2 , are needed to sample such large D2 values. Triexponential IVIM parameters obtained with such very small b‐values have so far been reported only for the liver to our knowledge.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Table 1 provides an overview of currently published values. One thing to note is that D2 reported in Riexinger et al 15 is roughly by 1 order of magnitude larger than the D2 values reported in the other publications, 5,10,11,13,14 which most likely can be attributed to the lower minimal b‐value used in Riexinger et al 15 The optimization performed here is based on the assumption that these large D2 values are a good representation of the real values and that consequently very small b‐values, say below 1 s/mm 2 , are needed to sample such large D2 values. Triexponential IVIM parameters obtained with such very small b‐values have so far been reported only for the liver to our knowledge.…”
Section: Methodsmentioning
confidence: 96%
“…Here, f 1 and f 2 represent perfusion fractions, and D * 1 and D * 2 represent the pseudo-diffusion coefficients. 5,[10][11][12][13][14][15] These additionally obtainable quantitative parameters might be useful, for example, to separate benign and malignant lesions as it was demonstrated for biexponential IVIM (e.g., Cho et al and Murtz et al). 16,17 More interesting, however, might be the exploration of the nature of the triexponential IVIM effect, because it could unveil general properties of the IVIM effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 These findings are in line with earlier studies, where the intermediate pseudo-diffusion was speculated to be attributable to the freely diffusing water. 14,15,55 The investigated renal cell carcinoma demonstrated quite a different diffusion spectrum pattern compared to the healthy kidney. We argue that the decreased f interm and, at the same time, increased f slow , might be due to a mechanical hindrance of water motion caused by the diffusion-restricting elements such as cell membranes and macromolecules.…”
Section: Discussionmentioning
confidence: 98%
“…In the IVIM model, D and f value are indicators to reflect the true diffusion coefficient and perfusion information of the molecule, respectively. IVIM modalities have also been used in other cervical cancer studies [21,22]. However, the current IVIM technology still has shortcomings and has not been applied on a large scale in the clinic setting.…”
Section: Discussionmentioning
confidence: 99%